Upaya Meningkatkan Sopan Santun Mahasiswa dengan Mengimplementasikan Bimbingan Kelompok Berbasis Hadits - Jannati, Zhila; Hamandia, Muhammad Randicha; Razzaq, Abdur (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The nobility of a person can be reflected in the presence of good manners in him. People who have high manners will be able to relate well to other people and can even become people who are really liked and missed by other people. This research on